Preparação e estudo de reatividade de sistemas catalíticos, a base de zirconocenos, frente à reação de homo- e copolimerização de eteno - Freitas, Alan John Duarte de (2007)
Catalytic systems based on zirconoces which are able to polymerize ethene have been studied. Structural modifications on the basic catalytic precursor, diphenylmethylidene(η5- cyclopentadienyl)(η5-9-fluorenyl) zirconium dichloride (5a) have been carried out. The catalytic precursors 5a and bis(para-fluorophenyl)methylidene(η5-cyclopentadienyl)(η5-9- fluorenyl)zirconium dichloride (5b) were synthesized, as well the pre-ligand (1- cyclopentadienyl)(9-fluorenyl)[1,1-bis(para-methoxyphenyl)]methane (3c). Complex Ph2C(Cp)(Flu)ZrCl2 was supported on silica by two different techniques. i) directly on silica, grafting, and ii) on silica modified with MAO. Catalytic tests on homopolymerization of ethene and copolymerization of ethene/1- hexene reactions, using the catalytic precursor 5a, were carried out either on homogeneous and heterogeneous media. The polymers obtained were characterized and their properties were correlated with the reaction polymerization conditions. Three different reactors, under different reaction conditions, were employed to carried out polymerization reactions. Several analytical techniques were employed to characterize the pre-ligands, catalytic precursors, polymers, and supports obtained.